2017
DOI: 10.1177/1535370217712690
|View full text |Cite
|
Sign up to set email alerts
|

Next generation human skin constructs as advanced tools for drug development

Abstract: Many diseases, as well as side effects of drugs, manifest themselves through skin symptoms. Skin is a complex tissue that hosts various specialized cell types and performs many roles including physical barrier, immune and sensory functions. Therefore, modeling skin in vitro presents technical challenges for tissue engineering. Since the first attempts at engineering human epidermis in 1970s, there has been a growing interest in generating full-thickness skin constructs mimicking physiological functions by inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 128 publications
(152 reference statements)
0
58
0
1
Order By: Relevance
“…Integration of microfluidics and electrical sensing modality in 3D tumor microenvironment may provide a powerful platform to accurately and rapidly monitor the response of cancer cells to a series of drugs . In addition, the on‐a‐chip approach at small‐scale makes this platform also considerably cost‐effective for drug screening applications . Mori and co‐workers in a perfusable skin equivalent model with vascular channels coated with endothelial cells were able to measure the cell density and distribution following perfusion and the amount of drug absorbed into the vascular channel .…”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of microfluidics and electrical sensing modality in 3D tumor microenvironment may provide a powerful platform to accurately and rapidly monitor the response of cancer cells to a series of drugs . In addition, the on‐a‐chip approach at small‐scale makes this platform also considerably cost‐effective for drug screening applications . Mori and co‐workers in a perfusable skin equivalent model with vascular channels coated with endothelial cells were able to measure the cell density and distribution following perfusion and the amount of drug absorbed into the vascular channel .…”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
“…Scale bar = 100 μm at small-scale makes this platform also considerably cost-effective for drug screening applications. [101] Mori and co-workers in a perfusable skin equivalent model with vascular channels coated with endothelial cells were able to measure the cell density and distribution following perfusion and the amount of drug absorbed into the vascular channel. [102] Abaci and co-workers using a skin-ona-chip platform with a unique capability to recirculate the medium demonstrated that the cancer drug, doxorubicin, may have direct toxic effects on keratinocyte proliferation and differentiation.…”
Section: Melanoma-on-chipsmentioning
confidence: 99%
“…Topically applied drugs must permeate the epidermal barrier, whereas systemically delivered drugs are controlled by the endothelial barrier. Incorporating vasculature into bioengineered skin is essential for improving the lifespan, graftability, and for studying the systemic delivery of drugs from/to the skin …”
Section: In Vitro Models Of Vascularized Organsmentioning
confidence: 99%
“…Compared to the prevalent “classical” 3D skin models, the development of novel complex next‐generation skin models based on induced pluripotent stem cells (iPSCs) and microfluidic technology (“skin‐on‐chip”) or using 3D bioprinting techniques will offer promising tools for the study of the microbiota‐skin interplay. For example, the use of iPSC‐derived cells such as keratinocytes, fibroblasts and melanocytes has already led to the successful generation of a complex 3D skin model .…”
Section: D Skin Modelsmentioning
confidence: 99%
“…In this context, the use of immortalised N/TERT keratinocytes seems to be a valuable approach as N/TERT keratinocytes have similar characteristics to primary keratinocytes, and successful generation of 3D skin models using N/TERT keratinocytes has been reported. [25,26] Compared to the prevalent "classical" 3D skin models, the development of novel complex next-generation skin models based on induced pluripotent stem cells (iPSCs) and microfluidic technology ("skin-on-chip") [27,28] or using 3D bioprinting techniques [29] will offer promising tools for the study of the microbiota-skin interplay. For example, the use of iPSC-derived cells such as keratinocytes, fibroblasts and melanocytes has already led to the successful generation of a complex 3D skin model.…”
Section: It Is Per Se Sterile and Can Be Selectively Colonised By Spementioning
confidence: 99%